KUHN'S PARADIGM CONCEPT IN THE FIELD OF ACCOUNTING SCIENCE - BILA, Yuliya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the academic realm, a paradigm defines the overall methodology or theory that sets boundaries for research in a particular field. Thomas Kuhn developed a concept that describes the content, structure, and conditions for paradigm shifts in science. However, the lack of consensus regarding the applicability of this concept in accounting makes it a subject worthy of investigation. The aim of the article is to determine the feasibility of applying Kuhn's paradigmatic model in accounting science. The methodological basis of the research involves the application of scientific and specialized methods of cognition. Analysis and historical methods were employed to process literature sources and identify discussions regarding the use of Kuhn's paradigmatic concept. Deduction and analogy helped in determining the advantages and disadvantages of employing Kuhn's paradigm model in science. Synthesis and induction were used to draw conclusions regarding the potential use of the paradigmatic concept in accounting.The research characterizes the essence of Kuhn's paradigmatic concept and analyzes scientific works in accounting that have utilized this concept. The advantages of its application in accounting are highlighted, including the identification of key elements of the "disciplinary matrix" in accounting science, the formulation of the structure of scientific revolutions, and the justification of the connection between science and the scientific community in terms of values and influence. It is revealed that Kuhn's concept excludes the multiparadigmality of science—a situation where the coexistence of multiple paradigms and the synergistic effect of their functioning is possible. Conclusions are formulated regarding the potential use of Kuhn's paradigmatic concept in accounting science.
Keywords: Accounting as a Science; Multi-paradigm Nature of Accounting; Accounting Paradigm; Kuhn's Paradigmatic Concept